Merged reality for everyone - Carvalho, Fausto de (2017)
This article addresses some interesting challenges and business opportunities within the promising merged reality ecosystem, which offers the vision of bringing together virtual, augmented and physical realities, seamlessly. The article also links the current status of this field with exploratory research and development work carried out by Altice Labs.